Activities of aztreonam in combination with several novel β-lactam-β-lactamase inhibitor combinations against carbapenem-resistant Klebsiella pneumoniae strains coproducing KPC and NDM - Li, Xinhui; Zhang, Jisheng; Wang, Jianmin; Long, Wenzhang; Liang, Xushan; Yang, Yang; Gong, Xue; Li, Jie; Liu, Longjin; Zhang, Xiaoli (Frontiers in Microbiology, 2024)
Isolates coproducing serine/metallo-carbapenems are a serious emerging public health threat, given their rapid dissemination and the limited number of treatment options. The purposes of this study were to evaluate the in vitro antibacterial activity of novel β-lactam-β-lactamase inhibitor combinations (BLBLIs) against carbapenem-resistant Klebsiella pneumoniae (CRKP) coproducing metallo-β-lactamase and serine-β-lactamase, and to explore their effects in combination with aztreonam, meropenem, or polymyxin in order to identify the best therapeutic options. Four CRKP isolates coproducing K. pneumoniae carbapenemase (KPC) and New Delhi metallo-β-lactamase (NDM) were selected, and a microdilution broth method was used to determine their susceptibility to antibiotics. Time-kill assay was used to detect the bactericidal effects of the combinations of antibiotics. The minimum inhibitory concentration (MIC) values for imipenem and meropenem in three isolates did not decrease after the addition of relebactam or varbobactam, but the addition of avibactam to aztreonam reduced the MIC by more than 64-fold. Time-kill assay demonstrated that imipenem-cilastatin/relebactam (ICR) alone exerted a bacteriostatic effect against three isolates (average reduction: 1.88 log10 CFU/mL) and ICR combined with aztreonam exerted an additive effect. Aztreonam combined with meropenem/varbobactam (MEV) or ceftazidime/avibactam (CZA) showed synergistic effects, while the effect of aztreonam combined with CZA was inferior to that of MEV. Compared with the same concentration of aztreonam plus CZA combination, aztreonam/avibactam had a better bactericidal effect (24 h bacterial count reduction >3 log10CFU/mL). These data indicate that the combination of ATM with several new BLBLIs exerts powerful bactericidal activity, which suggests that these double β-lactam combinations might provide potential alternative treatments for infections caused by pathogens coproducing-serine/metallo-carbapenems.